Morphological and molecular data of Hepatozoon ursi in two brown bears (Ursus arctos) in Turkey - Akyuz, Muzaffer; Kirman, Ridvan; Guven, Esin (Folia parasitologica, 2020)
Species of Hepatozoon Miller, 1908 are vector-borne parasites that infect domestic and wild animals worldwide. Hepatozoon ursi Kubo, Uni, Agatsuma, Nagataki, Panciera et al., 2008 was reported from bears (Ursidae) in Japan and India. The present study represents the first report of infection with H. ursi in Turkish brown bears (Ursus arctos Linnaeus) by microscopic and molecular analysis. Two dead brown bears were found in Uzundere and Pasinler districts of Erzurum. Blood and visceral organ (spleen and liver) samples were delivered to laboratory by the Nature Conservation and National Parks officers. Detected gamonts were evaluated based on morphological features and confirmed as gamonts of H. ursi. The size of gamonts and parasitemia were 8.2 × 3.5 μm (6.9-8.7 × 3.0-3.9 μm; n = 12) and 0.6% (6/1000 leukocytes), respectively. The blood and visceral organ samples were positive for species of Hepatozoon by PCR targeting partial sequence of 18S rDNA. Sequence analysis of newly obtained sequences of H. ursi showed 98.8-100% identity with previously sequenced isolates of H. ursi. Sequences of H. ursi from Erzurum were identical to each other and showed 100% identity with isolates of H. ursi from ticks Ixodes ricinus (Linnaeus), Rhipicephalus turanicus Pomerantzev and Hyalomma marginatum Koch collected from two brown bears in Turkey (GenBank accession numbers MN463021, MN463022, MN905023). Analysis of partial sequences of the 18S rRNA gene of H. ursi showed that Turkish isolates differ in NT substitutions found at three different positions [72 (A→G), 537 (A→G) and 570 (A→T)]. This study provides morphological and molecular data of H. ursi infection in brown bears from two districts of Erzurum, Turkey. Further studies are needed to elucidate whether brown bears have any eco-epidemiologic importance in the life cycle of H. ursi in wildlife.
Keywords: Liver; Animals; Eucoccidiida; RNA, Ribosomal, 18S; klíště; játra; hepatozoonosis; slezina; krev; Ursidae; Blood; Turkey; PCR; Phylogeny; Turecko; klíšťata; medvědovití; Ticks; RNA ribozomální 18S; Spleen; zvířata; fylogeneze; Ixodes; wildlife